Aggregatibacter actinomycetemcomitans dan Porphyromonas gingivalis: Bakteri Destruksi Tulang Alveolar - Octarina; Berliana, Stefhanie (Jurnal Kedokteran Gigi Terpadu, 2024)
The oral cavity is a suitable habitat for various types of bacteria, including Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis. Both of these bacteria can damage periodontal tissues, including alveolar bone, through various mechanisms. Prevention against these bacteria can be accomplished by maintaining oral hygiene. The purpose of this literature review was to provide information about bacteria that can cause damage to alveolar bone and ways to prevent it. The results of this literature review would provide information about the mechanisms of Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis bacteria in causing alveolar bone damage, as well as ways to prevent these bacteria.